Sistem Informasi Manajemen Jemaat Berbasis Web Untuk Meningkatkan Efisiensi Pelayanan Gereja Pantekosta Serikat di Indonesia - Oktavianus, Yohanes; Riadi, Aditya Akbar; Evanita, Evanita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Managing congregation data and church activity schedules manually often leads to errors or possibly data loss such as, limited access to information, and potential recording errors. The purpose of this research is to develop a custom-made web-based congregation and church schedule management information system to support service efficiency at GPSDI Juwana. The system includes the ability to manage church data, activity schedules, and real-time reports that can be accessed by administrators and authorized users. The system was developed using the “waterfall” development methodology through the phases of requirements analysis, design, implementation and testing. The test results show that the system can improve administrative efficiency, minimize data entry errors, and make information more accessible to all parties involved. The developed system can also reduce church administrators' errors when managing church data by 70%. The system aims to be an innovative solution that supports the digitalization of church worship today.